Induction of Tolerance to Fully Allogeneic Pulmonary Allograft by Adenosine A2A Receptor Agonist in MHC-defined CLAWN Miniature Swine. (July 2018) - Sahara, Hisashi; Sekijima, Mitsuhiro; Murokawa, Takahiro; Iwanaga, Takehiro; Ariyoshi, Yuichi; Ichinari, Yurika; Shimizu, Akira; Yamada, Kazuhiko
Abstract : Introduction: Adenosine has been found on immune cells such as neutrophils, macrophages, T-cells as well as on endothelial cells and the agonist of the adenosine A2A receptor (A2A R), one of four subtypes of the adenosine receptor family is known to potently attenuate lung ischemia-reperfusion injury (IRI). However, the long-term effects of this agonist on lung allograft survival remain unclear especially in large animals. The aim of this study is to investigate whether A2A R agonist has beneficial effects on pulmonary allograft survival using MHC-defined CLAWN miniature swine. Methods: Twelve swine received fully MHC-mismatched lungs with 12 days of FK506 (35-45 ng/ml). In Group 1, six recipients received FK506 alone. In Group 2, three recipients were transplanted with lungs from brain-dead (BD) donors induced by subdural balloon inflation for 6 hours before organ procurement in order to examine whether BD affects the graft survival. In Group 3, three recipients were transplanted with lungs from BD donors treated with adenosine A2A R agonist (CGS21680: 5 μg/kg/min) starting 3 hours after BD induction. All recipients in group 3 additionally received the same dose of CGS21680 for 3 hours after reperfusion of the graft. Graft function was assessed by blood gases from the graft pulmonary vein (PV) and serial lung biopsies. The expression of mRNA of proinflammatory cytokines of the grafts (IL-1β and IL-6) were quantified by real-time RT-PCR. Results: All grafts in Group 1 was rejected by day 63 with diffuse mononuclear cell infiltrates associated with intra-alveolar hemorrhage and capillary congestion. All three animals in Group 2 completely rejected the grafts by day 35, indicating rejection of grafts was accelerated by donor BD. In Group 3, CGS21680 was effective on early graft function. PO2 of graft PV in group 3 was higher than that of Group 2 (552 ± 22 vs. 414 ± 106 mmHg at 2 hour; 553 ± 19 vs. 349 ± 28 mmHg at day 2) associated with fewer inflammatory cell infiltrates both at 2-hour and day 2 biopsies. Up-regulation of proinflammatory cytokines in group 3 was markedly reduced at the time of organ procurement as well as at 2 hour and day 2 compared with Group 2. Although we lost one animal due to severe pneumonia at day 21, other two animals accepted the grafts over 150 days even after cessation of 12 days of FK506. Anti-donor T-cell responses assessed by MLR and anti-donor IgG development assessed by FACS was significantly reduced in Group3. Moreover, higher percentage of FoxP3-positive infiltrating cells were detected in Group 3, suggesting adenosine-mediated production of regulatory T cells. Conclusions: Not only short-term effects, treatment of adenosine A2A R agonist with 12 days of FK506 facilitates induction of tolerance to fully allogeneic lung. This is the first evidence of successful induction of tolerance with short course of FK506 with adenosine A2A R agonist in a clinically relevant large animal model.